Searching for the Turning Point to Bronze Age Societies in Southern Portugal : Topics For A Debate - Soares, Joaquina (2021)
This contribution aims to address the Chalcolithic/Bronze Age transition in southern Portugal from a socio-economic perspective. The starting point is the extensive archaeological fieldwork that took place at the Chalcolithic fortification of Porto das Carretas (Luz Territory) on the left bank of the Middle Guadiana river, integrated in multi-geographical scales. Our main goal is to arrive ‘just in time’ at the dawn of southwest Middle Bronze Age societies, trying to understand their formation. In chronological terms, the deconstruction of Chalcolithic societies began in central-southern Portugal around 2500 cal BC, coincident with the rise of the Bell Beaker phenomenon. At Chibanes (Estremadura), domestic architectures and the wall of the fortification were damaged, with no signs of any reconstruction. Other sites, such as Porto das Carretas and Monte da Tumba (Alentejo) had been rebuilt by Bell Beaker elites, showing a clear cut with the previous architectural programs. Ditched enclosures collapsed c. 2200-2000 cal BC, but the construction of the latest ditches of the enclosure systems did not extend beyond 2500-2400 cal BC. The construction of large tholos-type collective funerary monuments was replaced by individual graves, although sometimes with the reuse of the previous collective tombs. This trend to single graves reached a peak in the Early/Middle Bronze Age. The crisis of the Chalcolithic society and its collapse in the second half of the 3rd millennium cal BC allowed more unequal and hierarchical regional Bronze Age societies throughout southern Iberia, along with craft specialisation/oriented groups (socio-economic specialisation of labour) in metallurgy and textile activities (mainly linen production). At the same time, the political economy grew more differentiated, controlled by powerful chiefs of the ‘Southwest Bronze Age Culture’, or ruled by the early state of El Argar in the southeast.